2016
DOI: 10.1002/bkcs.11035
|View full text |Cite
|
Sign up to set email alerts
|

Energetic and Frictional Effects in the Transport of Ions in a Cyclic Peptide Nanotube

Abstract: The effects of geometric restraints and frictional parameters on the energetics and dynamics of ion transport through a synthetic ion channel are investigated using molecular dynamics (MD) simulations for several different ions. To do so, potential of mean force profiles and position‐dependent diffusion coefficients for Na+, K+, Ca2+, and Cl− transport through a simple cyclic peptide nanotube, which is composed of 4× cyclo[−(D‐Ala‐Glu‐D‐Ala‐Gln)2−] rings, are calculated via an adaptive biasing force MD simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…We chose R c ¼ 10Å because previous MD simulation studies revealed that the diffusion coefficients of ions begin to decrease nearly 10 Å away from the channel entrance of cyclic peptide nanotubes (CPNs) that possess a similar structure to the model nanopore in this study. 29,30 Then, the ion current for ion i can be evaluated as…”
Section: Implementation Of Position-dependent Diffusion Coefficients ...mentioning
confidence: 99%
See 2 more Smart Citations
“…We chose R c ¼ 10Å because previous MD simulation studies revealed that the diffusion coefficients of ions begin to decrease nearly 10 Å away from the channel entrance of cyclic peptide nanotubes (CPNs) that possess a similar structure to the model nanopore in this study. 29,30 Then, the ion current for ion i can be evaluated as…”
Section: Implementation Of Position-dependent Diffusion Coefficients ...mentioning
confidence: 99%
“…21,[34][35][36][37] Ion-related parameters such as the LJ parameters and diffusion coefficients in bulk water and inside the nanopore are presented in Table 1 where the values of D chn i are set to be 0.4 D blk i for K + , Na + , and Cl À on a basis of the molecular dynamics (MD) simulation results for the position-dependent diffusion coefficients of ions inside a cyclic peptide nanotube (CPN). 29,30 We used the ion radii from the Chemistry at Harvard Macromolecular Mechanics (CHARMM) force field instead of the hydrodynamic radii of ions because our previous MD simulations showed that the ions are partially dehydrated inside a small nanopore like the model system we used in this study. 10,42 A two-dimensional contour map and a one-dimensional profile for the relative position-dependent diffusion coefficient of ion i used in our simulations are illustrated in Figure 2.…”
Section: Implementation Of Position-dependent Diffusion Coefficients ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclic compounds have been the center of attention of many chemists . Recently, cyclic peptides (CPs) have been noted for their application in chemistry and biology . They are useful in many fields of applications such as antibacterial agents, molecular transport systems, electronics, and other applications .…”
Section: Introductionmentioning
confidence: 99%